Beginning VFX with Autodesk Maya : create industry-standard visual effects from scratch - Kumar, Abhishek, 1989- (Apress, 2022)
Dive into the nuances of visual effects (VFX) design, from planning to execution, using Autodesk Maya. This book introduces the methods and techniques required for your first foray into 3D FX generation from scratch. You will start with the fundamentals of visual effects, including a history of VFX, tools and techniques for creating believable visual effects, and popular tools used in the industry. Next, you are introduced to Autodesk Maya and its various components that make it a favorite among professionals. You will learn how to create rigid body collisions and simulate realistic particles such as dust, fire, water, and more. This book also presents strategies for creating a vortex, rain, hair, fluids, and other soft body simulations and also demonstrates nature element simulations for computer-generated production. At the end of the book, there is a capstone project to make your own visual effects scene in a practical way. After going through this book, you will be able to start building computer-generated visual effects from your imagination through to production. What You Will Learn Understand the basic physics behind effect creation Create 3D visual effects scenes from scratch Know the details of dynamic simulation in the computer generation space using various functionalities available in Autodesk Maya.